Identifikasi Penyebab Cacat Produk Corrugated Medium Paper Menggunakan Metode Fmea (Failure Mode & Effect Analysis) - Ifan Aly Rifqi; Hendi Herlambang; Tri Ngudi Wiyatno (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to identify the causes of production defects in Corrugated Medium Paper (CMP) products at a paper manufacturing company using the Failure Mode and Effect Analysis (FMEA) method. Based on observations and production data from the period of September to December 2024, it was found that the product defect rate reached 2%, exceeding the company’s target of 0.3%. The main type of defect identified was unstable grammage, with the highest Risk Priority Number (RPN) of 128, indicating the need for special attention. The FMEA method was applied through nine stages to analyze failures in the production process. The analysis results show that the primary causes of product defects involve human factors, machinery, raw materials, methods, and the environment. One significant cause was operator inaccuracy during the raw material sorting process, substandard raw material quality, and lack of maintenance on machine components such as the Auto Valve Dilution. The analysis was complemented with a Fishbone Diagram to identify the root causes of the problem. Improvement recommendations include enhanced supervision during raw material sorting, more rigorous inspections every 30 minutes during production, and regular checks and repairs on critical machine components. The implementation of these measures is expected to minimize production defects, improve product quality, increase productivity, and reduce company losses